Where are we heading? Challenges in evidence-based severity assessment. (February 2020) - Keubler, Lydia M; Hoppe, Nils; Potschka, Heidrun; Talbot, Steven R; Vollmar, Brigitte; Zechner, Dietmar; Häger, Christine; Bleich, André
Evidence-based severity assessment in laboratory animals is, apart from the ethical responsibility, imperative to generate reproducible, standardized and valid data. However, the path towards a valid study design determining the degree of pain, distress and suffering experienced by the animal is lined with pitfalls and obstacles as we will elucidate in this review. Furthermore, we will ponder on the genesis of a holistic concept relying on multifactorial composite scales. These have to combine robust and reliable parameters to measure the multidimensional aspects that define the severity of animal experiments, generating a basis for the substantiation of the refinement principle.